Maksim Sopan Santun Pada Pembelajaran Online Sekolah Dasar 013 Gotong Royong Kota Samarinda - Suryani, Siti; Hudiyono, Yusak; Agustian, Jaka Farih (Universitas Mulawarman, 2018)
This study aims to describe the forms of maxims, obedience to maxims, and violation of the maxims of politeness in online learning at SD N 013 gotong royong, Samarinda city, which aims to describe pragmatic research studies. The research subject is online learning. The object of research is the observance of the maxim of politeness and the violation of the maxim of politeness in online learning that takes place at school. This type of research is a qualitative descriptive method. Techniques Data collection is done by observing methods. The data analysis technique is to clarify and classify the data. The results showed that there were 35 utterances of teachers and students in online learning at SD Negeri 013 gotong royong in the city of Samarinda which were identified as forms of politeness maxims. 27 utterances of obedience to the maxim of politeness, and 8 utterances of violation of the maxim of politeness to teachers and students. The data on compliance with maxims and violations consist of four utterances of obedience to the maxim of wisdom and two utterances of violation of the maxim of wisdom. Three utterances of obedience to the maxim of generosity and one utterance of violation of the maxim of generosity. Five utterances of respecting the maxim of respect and no utterances of violation of the maxim of appreciation. There are four utterances of obeying the maxim of simplicity and four utterances of violating the maxim of simplicity. Six utterances of compliance with the maxim of consensus and one utterance of violation of the maxim of consensus. Five utterances of compliance maxim of sympathy and no utterances of violation of maxim of sympathy.